1997
DOI: 10.1097/00005344-199710000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Infarct Size-Reducing Effect of Ischemic Preconditioning Is Related to α1b-Adrenoceptors But Not to α1a-Adrenoceptors in Rabbits

Abstract: In rabbits and rats, both stimulation of alpha-adrenoceptors and ischemic preconditioning (PC) reduce infarct size. Activation of alpha1b-adrenoceptors play an important role in the PC effect on ventricular function in rats. However, the alpha1-adrenoceptors have not been reported to be related to the PC effect in rabbits, because the infarct size-reducing effect of PC is not blocked by the nonselective alpha-adrenoceptor antagonist, phenoxybenzamine (POB) or by the alpha1-adrenoceptor antagonist, BE2254. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 35 publications
4
19
0
Order By: Relevance
“…α1-Antagonists have negative effects on adaptive cardiac processes in vitro and in animal models in vivo [132, 153155] (Table 3), supporting the data from pharmacology gain of function (Table 1). However, the pharmacologic tools can have nonspecific effects, and are inadequate to distinguish α1-subtypes in vivo.…”
Section: Evidence From α1-ar Loss Of Function In Animal Models (Table 3)supporting
confidence: 60%
“…α1-Antagonists have negative effects on adaptive cardiac processes in vitro and in animal models in vivo [132, 153155] (Table 3), supporting the data from pharmacology gain of function (Table 1). However, the pharmacologic tools can have nonspecific effects, and are inadequate to distinguish α1-subtypes in vivo.…”
Section: Evidence From α1-ar Loss Of Function In Animal Models (Table 3)supporting
confidence: 60%
“…Consistent with our data, Gao et al [24] found that expression of CAM a 1B -ARs in the heart-targeted transgenic mouse does not protect the heart from ischemic injury. However, others have reported that ischemic preconditioning of rat and rabbit hearts is mediated by a 1B -ARs [25][26][27]. It is possible that the a 1 -AR subtype that mediates ischemic preconditioning is different in the mouse heart than in rabbit or rat hearts.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the inhibition of glycogenolysis, there are several mechanisms for PC, such as the activation of adenosine receptors, 6 1b-adrenoceptors, 7 bradykinin B2 receptors 8 and oxyradicals, 9 that can independently activate protein kinase C and the opening of the mitochondrial KATP channel. Therefore, these mechanisms might also contribute to the marked effect of the combination of NMDN and PC.…”
Section: Discussionmentioning
confidence: 99%